Efek Induksi Diabetes Mellitus Tipe -1 Pada Histopatologi Pancreas Tikus Putih (Rattus Norvegicus) - Maria Margaretha (Fakultas Kedokteran Hewan Universitas Wijaya Kusuma Surabaya, 2016)
This study aims to determine induction of type I diabetes mellitus to changes histopathological picture of the pancreas in rats (Rattusnorvegicus). The research sample used was a albino rat (Rattus norvegicus) as many as 12. Albino rat were randomly divided into 2 groups with each group 6 animals, treatment group as a control that is not induced alloxan (P0), the treatment group induced alloxan with the dose of 50 mg / kg (P1), rats induced by alloxan for 3 days intraperitoneally after it conducted checks of blood sugar by means of glucometers, on day 4 continued therapy (P2), until day 8 do a necropsy to take samples of pancreas then made preparations Histopathological to do microscopic observation. The results of data analysis using the Kruskal Wallis of pancreas are edema with value of P = 0.011, P = 0.011 acinar necrosis, inflammation and perivasculer P value = 0.017 infiltrates P value hemmorage and fat necrosis = 0,172. All P values greater than 0.05 means no differences were found with the data distribution standard normal distributed data. It is concluded that there are some severe lesion in the pancreas with diabetic alloxan induced.